Poor response to azithromycin in cutaneous leishmaniasis leading to a premature interruption of a multicentric phase III clinical trial in Brazil - Toledo Junior, Antonio (2014)
Introduction Parenteral antimony-based compounds are still the standard of care for cutaneous leishmaniasis (CL) treatment in many countries, despite their high toxicity. Previous studies showed that oral azithromycin could be an option for CL treatment. The aim of this study was to evaluate efficacy and safety of oral azithromycin (AZ) for CL treatment compared with injectable meglumine antimoniate (MA). Methods This was a randomized, open-label, 2-arm, non-inferiority clinical trial. Treatment-naïve patients with localized CL were treated with MA (15mg/kg/day up to 1,215mg) or AZ (500mg/day) during 20 consecutive days. The primary efficacy end point was a CL cure 90 days after treatment completion. The analysis was performed with intention-to-treat (ITT) and per protocol (PP) analyses. After an anticipated interim analysis, the study was interrupted due to the high failure rate in the azithromycin group. Results Twenty-four volunteers were included in each group. The MA group had a higher cure rate than the AZ group with the ITT and PP analyses, which were 54.2% versus 20.8% [relative risk (RR) 1.97; 95% confidence intervals (95%CI) 1.13-3.42] and 72.2% versus 23.8% (RR 3.03; 95%CI 1.34-6.87), respectively. No unexpected adverse events were observed. Conclusions Azithromycin is ineffective for CL treatment and does not seem to have a role in the therapeutic arsenal for CL.